2016
DOI: 10.1002/cbic.201600164
|View full text |Cite
|
Sign up to set email alerts
|

Reduction‐Responsive Guanine Incorporated into G‐Quadruplex‐Forming DNA

Abstract: Stimulus-responsive biomolecules are attractive targets to understand biomolecule behaviour as well as to explore their therapeutic and diagnostic applications. We demonstrate that a reduction-responsive cleavable group (chemically caged unit) introduced into the guanine ring enables modulation of the secondary structure transition of an oligonucleotide in a reduction-responsive and traceless manner leaving the unmodified oligonucleotide of interest. This simple but robust strategy could yield a variety of sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…[ 61 ] Ikeda and coworkers recently incorporated a 4‐nitrobenzyl moiety at the O6 position of guanosine (G NB ) as a reduction‐responsive group that can be removed in response to both chemical (sodium hydrosulfite) and enzymatic (nitroreductase in the presence of NADH) stimuli. [ 62 ] This modification blocks Watson–Crick base‐pairing of the sequence containing the modification. The authors incorporated G NB into a thrombin‐binding aptamer (TBA), and showed that chemical reduction of the NB group was required for the aptamer to fold into its binding active G‐quadruplex state.…”
Section: Chemically Induced Switchingmentioning
confidence: 99%
“…[ 61 ] Ikeda and coworkers recently incorporated a 4‐nitrobenzyl moiety at the O6 position of guanosine (G NB ) as a reduction‐responsive group that can be removed in response to both chemical (sodium hydrosulfite) and enzymatic (nitroreductase in the presence of NADH) stimuli. [ 62 ] This modification blocks Watson–Crick base‐pairing of the sequence containing the modification. The authors incorporated G NB into a thrombin‐binding aptamer (TBA), and showed that chemical reduction of the NB group was required for the aptamer to fold into its binding active G‐quadruplex state.…”
Section: Chemically Induced Switchingmentioning
confidence: 99%
“…A nitrobenzyl (NB) group has also been introduced at O6 of a guanine to modulate the conformational properties of a G-quadruplex structure-forming single-stranded DNA [ 28 ]. The dG NB phosphoramidite was synthesized and incorporated into the sequence of a thrombin-binding DNA aptamer (TBA, at the 5’-end) prone to form a G-quadruplex structure ( Scheme 7 ).…”
Section: Reviewmentioning
confidence: 99%
“… Incorporation of O 6 -(4-nitrobenzyl)-2’-deoxyguanosine into an ON prone to form a G-quadruplex structure, preventing it from forming this quadruplex when protected and allowing it under reducing conditions [ 28 ]. …”
Section: Reviewmentioning
confidence: 99%
“…6 In a similar way, our group has recently developed O 6 -(4-nitrobenzyl)-modified guanosine (G NB , Figure 1B, a(iii)), which was incorporated into a Gquadruplex-forming DNA aptamer (15-mer). 7,8 It was demonstrated that both chemical and enzymatic reduction successfully trigger G-quadruplex formation ( Figure 2B). 7 Since the target protein binding function of such aptamers necessitates a secondary structure, such as a G-quadruplex, it is reasonably expected that the ability of the chemically caged aptamer to bind to its target protein can be controlled by reductive stimuli or environments in an OffOn manner.…”
Section: Introduction Sites For Responsive Unitsmentioning
confidence: 98%
“…7,8 It was demonstrated that both chemical and enzymatic reduction successfully trigger G-quadruplex formation ( Figure 2B). 7 Since the target protein binding function of such aptamers necessitates a secondary structure, such as a G-quadruplex, it is reasonably expected that the ability of the chemically caged aptamer to bind to its target protein can be controlled by reductive stimuli or environments in an OffOn manner. Saneyoshi et al developed O 4 -(4-nitrobenzyl)-modified thymine (T NB , Figure 1B, a(iv)) and introduced it into DNA 13-mers.…”
Section: Introduction Sites For Responsive Unitsmentioning
confidence: 98%